Knowledge-based engineering and computer vision for configuration-based substation design - Nordvall, Erik; Wiberg, Anton; Tarkian, Mehdi (Frontiers in Mechanical Engineering, 2023)
In this paper an automated approach for design and production preparation of electrical substations is outlined. As the increase in electrification pose new demands on power delivery, the quality of the distribution system is paramount. Substations are a critical part of power grids that allow for control and service of the electrical distribution system. Substations are currently developed in a project based and manual intensive manner with a high degree of manual work and lengthy lead times. Substations are primarily sold through tenders and the inherent need for engineering-to-order activities. Although necessary, these activities present a paradox as tender processes must be agile and fast. To remedy this shortcoming, this paper outlines a knowledge capture and reuse methodology in order to standardize and automate the product development processes of substation design. A novel framework for substation design is presented which implements knowledge-based engineering and artificial intelligence methods in computer vision to capture knowledge. In addition, a product configuration system is presented, utilizing high level cad templates. The proposed framework has decreased the time to create a 3D model from basic single line diagram in an automated fashion. Ultimately the framework will allow substation design companies to increase competitiveness through automation and knowledge management and enabling more tenders to be answered without losing engineering quality.